Determination of Essential and Heavy Metals and Phytochemical Screening of Lepidium sativum Seeds from Libya - Soad H. Alsoul; Lutfiyah A. Rahouma; Hana A. Elshaflu (African Journal of Advanced Pure and Applied Sciences, 2026)
The study investigated Lepidium sativum seeds, Lepidium sativum, which were obtained from herbal shops in Libya, to analyze their phytochemical makeup and essential metal and heavy metal content. Phytochemical testing of the aqueous, methanolic, and acetone extracts identified the presence of alkaloids, saponins, flavonoids, phenols, glycosides, carbohydrates, proteins, and amino acids while tannins and anthraquinones were absent. The essential metals showed high levels of potassium, magnesium, calcium, sodium, phosphorus, and iron. The sample contained different heavy metals which were present in extremely small amounts with Pb measured at 0 µg/100g and Ni at 28.5 ± 1.32 µg/100g and Cu at 35.98 ± 1.05 µg/100g and Hg at 0.277 ± 0.074 µg/100g and Mn at 0.004 ± 0.003 µg /100g. The scientists prepared the samples by first dry ashing 2 grams of powdered seeds at 550 degrees Celsius for 3 hours and then they digested the ash with 12.5 milliliters of HNO₃ before they diluted it to 100 milliliters. The results showed that all detected metals were below the permissible safety limits. The results demonstrate that Lepidium sativum seeds which are sold in stores contain important essential minerals and bioactive substances while showing minimal heavy metal pollution which makes them safe for use in dietary and traditional healing purposes.